Copper removal from ammoniacal spent etchant by using magnetic nanoparticles - (:unkn) unknown (My University, 2018)
Using magnetic nanoparticles (MNPs) is becoming popular method to remove heavy metal ions from different wastestreams because it is simple, low-cost and effective. In this study, the bare and polymer coated Magnetite Iron Oxide($Fe_3O_4$) MNPs were assessed for their adsorption capability in removing cupric ($Cu^{2+}$) ions from ammoniacal spentetchant solution, which is originated from the production of Printed Circuit boards (PCBs). The polymers used to coatthe MNP in this study were chitosan, levan and oleic acid. The batch adsorption experiments were conducted at atemperature of 20oC and the pH of the solution was between 9.0 and 9.5. Experimental results showed that adsorptionwas achieved within 2 hours, and the maximum amount of $Cu^{2+}$ ions adsorbed by unit weight of MNP was observed bychitosan coated MNP with an adsorption capacity of 125 mg $g^{-1$}. In addition, Zeta potential measurements showed thatall MNPs used in adsorption tests had negative surface charges at around pH 9.0. The more negatively surface chargeMNPs the more copper ions they can adsorb. From this experiment it can be concluded that chitosan coated magneticnanoparticle can be widely used for the removal of copper ions from water and wastewaters.